Assessment of hemodynamic changes in patients with renal artery stenosis by means of the cine MR phase-contrast technique - Schönberg, Stefan; Knopp, Michael V.; Bock, Michael; Kallinowski, Friedrich; Just, Armin; Essig, Marco; Hawighorst, Hans; Zuna, Ivan; Schad, Lothar R.; Allenberg, Jens-Rainer; Kaick, Gerhard van (Der Radiologe, 1997)
Purpose: To evaluate the use of high-temporal resolution cine MR phase-contrast flow measurements for assessment of flow dynamics in renal artery stenosis (RAS). Material and methods: In a dog model, cine MR flow measurements were validated by comparing the MR flow data to an invasive transit-time ultrasound reference technique for different degrees of RAS. Cardiac-gated MR flow curves were recorded in 56 renal arteries of 28 patients with a temporal resolution of at least 32 ms. In all cases RAS was confirmed by digital subtraction angiography (DSA). Abnormalities of flow dynamics were assessed in the calculated flow curves using the MR parameters mean flow, maximum velocity, and time to systolic maximum. - Results: By means of the MR blood flow parameters high-grade stenoses ( >50 %, n = 23) were detected with sensitivity of 100 % and specificity of 94 % with reference to DSA. The overall differentiation between stenoses (n = 37) and non-stenosed vessels (n = 19) revealed a sensitivity of 87 % and a specificity of 100 %. - Conclusion: Analysis of cardiac-gated MR flow curves provides a non-invasive method to assess the hemodynamic significance of RAS and thus allows a functional evaluation in relation to the morphologic characteristics of the stenosis.
Gesehen am 19.09.2023